Estimating exchange market pressure and the degree of exchange market intervention for Finland during the floating exchange rate regime - Mika Pösö; Mikko Spolander (Bank of Finland, 1997)
In this paper, we use a fairly simple monetary macro model to calculate the quarterly measures of exchange market pressure and the degree of the Bank of Finland's intervention during the time the markka was floated.Exchange market pressure measures the size of the exchange rate change that would have occurred if the central bank had unexpectedly refrained from intervening in the foreign exchange market.Intervention activity of the central bank is measured as the proportion of exchange market pressure relieved by foreign exchange interventions. According to the measures, exchange market pressure decreased during the course of the markka float.Looking at the float as a whole, we cannot say whether depreciation or appreciation pressure was clearly dominant.However, the quarterly exchange market pressure was more often negative than positive. The intervention indices indicate that the Bank of Finland limited the quarterby-quarter changes in the external value of markka almost totally allowing markka to drift slowly towards its underlying free-float equilibrium value.The estimates of intervention activity during periods of appreciation and depreciation pressure diverged most in 1994 and 1996.In 1994, depreciation pressure was dampened more carefully than appreciation pressure.In 1996, on the other hand, the Bank of Finland reacted much more cautiously to appreciation pressure.Overall, the Bank of Finland's reactions to appreciation pressure seem to have varied markedly, while its reactions to depreciation pressure seem to have been more consistent.
URN:NBN:fi:bof-20140807269
Keywords: 330; exchange market pressure; exchange market intervention; floating exchange rate regime